Modular One-Pot Strategy for the Synthesis of Heterobivalent Tracers - Bailly, Thibaud; Bodin, Sacha; Goncalves, Victor; Denat, Franck; Morgat, Clement; Prignon, Aurelie; Valverde, Ibai E. (ACS medicinal chemistry letters, 2023)
Bivalent ligands, i.e., molecules having two ligands covalently connected by a linker, have been gathering attention since the first description of their pharmacological potential in the early 80s. However, their synthesis, particularly of labeled heterobivalent ligands, can still be cumbersome and time-consuming. We herein report a straightforward procedure for the modular synthesis of labeled heterobivalent ligands (HBLs) using dual reactive 3,6-dichloro-1,2,4,5-tetrazine as a starting material and suitable partners for sequential SNAr and inverse electron-demand Diels-Alder (IEDDA) reactions. This assembly method conducted in a stepwise or in a sequential one-pot manner provides quick access to multiple HBLs. A conjugate combining ligands toward the prostate-specific membrane antigen (PSMA) and the gastrin-releasing peptide receptor (GRPR) was radiolabeled, and its biological activity was assessed in vitro and in vivo (receptor binding affinity, biodistribution, imaging) as an illustration that the assembly methodology preserves the tumor targeting properties of the ligands.